2005
DOI: 10.1080/09537100400004355
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-platelet interaction in pregnancies complicated with preeclampsia

Abstract: This article presents further evidence that changes from the nonpregnant to the pregnant state are associated with hemostasis activation as an integrated part of an inflammatory reaction that is even more pronounced when pregnancy is complicated with preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…There is a solid body of evidence supporting platelet activation in patients with preeclampsia and fetal growth restriction [1,9,11,13,38,48,50,59,62,64,65,74,75,82,86,88,96,99,102,108,116,128,137]. Indeed, elevated maternal plasma and platelet expression of markers for platelet activation, including P-selectin (CD62p) [48,68,74,75,86,128,137,138], Annexin V [34,50,128], and sCD40L concentrations [2,78,95,104], were reported in patients with these pregnancy complications.…”
Section: Platelet Activation and Pregnancy Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a solid body of evidence supporting platelet activation in patients with preeclampsia and fetal growth restriction [1,9,11,13,38,48,50,59,62,64,65,74,75,82,86,88,96,99,102,108,116,128,137]. Indeed, elevated maternal plasma and platelet expression of markers for platelet activation, including P-selectin (CD62p) [48,68,74,75,86,128,137,138], Annexin V [34,50,128], and sCD40L concentrations [2,78,95,104], were reported in patients with these pregnancy complications.…”
Section: Platelet Activation and Pregnancy Complicationsmentioning
confidence: 99%
“…There are inconsistent reports concerning the degree of platelet activation and the release of vasoactive products during normal pregnancy [8,51,60,113,114]. Women who develop obstetric complications, such as preeclampsia and fetal growth restriction, have a higher degree of platelet activation than both normal pregnant and non-pregnant women [1,9,11,13,38,48,50,59,62,64,65,74,75,82,86,88,96,99,102,108,116,128,137]; however, little information is available regarding the association between maternal platelet activation and preterm labor (PTL) [117].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 P-selectin is a marker located at the junction between the endothelium and platelets. 14 Vascular endothelial dysfunction and neutrophil activation have been well documented in PE, 1,6,15 and the endothelial expression and regulation of platelet activating receptors have also been described. 16 Platelets from PE patients have been found to exhibit no significant thrombopoietin potentiation, 17 which is quite important in platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…1 -5 Enhanced haemostasis is even more pronounced when pregnancy is complicated by pre-eclampsia (PE) 1 and PE occurs in 6 -8% of all pregnancies worldwide. Research on the biomarkers of vascular endothelium and leucocyte activation has suggested that PE may arise from a maternal systemic inflammatory response associated with endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…This heightens the normal shift of haemostatic equilibrium toward hypercoagulability. As part of this generalized hypercoagulability status in pregnancy, evidence for enhanced platelet activation, observed in normotensive pregnancies [18], are further increased in women with preeclampsia giving rise to the formation of platelet-derived microthrombi in smaller vessels [20] and an associated disseminated intravascular coagulation [21]. Similar to changes in the coagulation parameters, changes in platelet activation status are recorded before gestational week 13 in PE.…”
Section: Haemostasis In Pregnancymentioning
confidence: 99%